Neuropsychiatric symptoms among older adults living in two countries in Central Africa (EPIDEMCA study) - (:unkn) unknown (My University, 2019)
Our study aimed at estimating the prevalence of neuropsychiatric symptoms and investigating associated factors among older adults living in two countries in Central Africa (Central African Republic [CAR] and Republic of Congo [ROC]).METHODS:The EPIDEMCA multicentre population-based study was carried out in rural and urban areas of CAR and ROC between 2011 and 2012 among people aged 65 and over. After cognitive screening using the Community Screening Interview for Dementia, participants with low performances underwent neurological examination including the brief version of the Neuropsychiatric Inventory Questionnaire (NPI-Q). Multivariate logistic regression analyses were performed to identify factors independently associated with neuropsychiatric symptoms in this population.RESULTS:NPI-Q data were available for 532 participants. Overall, 333 elderly people (63.7%) reported at least one neuropsychiatric symptom. The prevalence of neuropsychiatric symptoms was 89.9% (95% CI, 84.6-95.1) in participants with dementia, 73.4% (95% CI, 65.1-81.7) in participants with mild cognitive impairment (MCI), and 48.7% (95% CI, 42.9-54.6) in participants with no MCI nor dementia after neurological examination (P < 0.0001). The most common symptoms were depression, anxiety, and irritability. Participants living in Gamboma, with normal hearing and with friends in the community, were less likely to present neuropsychiatric symptoms. Physical disability, difficulties in eating, female sex, and dementia were significantly associated with neuropsychiatric symptoms.CONCLUSION:Neuropsychiatric symptoms are common among older people with neurocognitive disorders in CAR and ROC. Our results confirm those from previous studies in Nigeria and Tanzania. Nevertheless, knowledge of these symptoms remains limited in sub-Saharan Africa, hampering their appropriate management.
Keywords: African Research